Hydrodehalogenation of Haloarenes by a Sodium Hydride–Iodide Composite. Issue 7 (10th January 2017) - Ong, Derek Yiren; Tejo, Ciputra; Xu, Kai; Hirao, Hajime; Chiba, Shunsuke
Abstract: A simple protocol for hydrodebromination and ‐deiodination of halo(hetero)arenes was enabled by sodium hydride (NaH) in the presence of lithium iodide (LiI). Mechanistic studies showed that an unusual concerted nucleophilic aromatic substitution operates in the present process. Abstract : A simple protocol for hydrodebromination and ‐deiodination of halo(hetero)arenes was enabled by sodium hydride (NaH) in the presence of lithium iodide (LiI). Mechanistic studies show that an unusual concerted nucleophilic aromatic substitution operates in the present process.